Production of bioplastics with chemical and enzymatic modificated xylan (lignin- and arabinose-free) from sugarcane bagasse - Bueno, Danilo [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2025)
Hemicellulose is a renewable source to produce bio-based molecules with high added value. For this purpose, this study aimed to promote enzymatic and chemical modifications of xylan from sugarcane biomass to produce substrates as substitutes for scarce and expensive commercial xylan such as from beechwood and beachwood. Lignin- and arabinose-free xylans were produced through enzymatic and chemical treatments (using laccase (X3), α-L-arabinofuranosidase (X4) and H2O2 (X2)), compared to untreated/original xylan (X1). Xylan delignified with laccase (X3) showed interesting substrates as it induced a xylanase activity of 1350 IU/mL from Aspergillus versicolor growth, as a result of residual lignin removal, making xylan more accessible for enzymatic hydrolysis. These modified xylans were also used to produce bioplastics with potential technological applications that are sustainable, possibly biodegradable and obtained by a methodology that is easy to reproduce. The results indicate that the opacity (4.7%), moisture (7%) and solubility (35%) from bioplastic type 1 (B1: based on original xylan without modifications) showed that the presence of residual lignin contributed to a major opacity of the material, with moisture retention, increasing water solubility and decreasing tensile stress. It can be highlighted that the modifications of xylan resulted in improvements in the quality, integrity, and resistance of bioplastics, addressing the lack of information in the literature regarding the production and evaluation of xylan-based bioplastics described to date. Furthermore, this study addresses the scarcity and high cost of commercially available xylan by producing and evaluating an economically viable alternative, obtained through a simple and efficient protocol.